Peran Dewan Pastoral Paroki dalam Pelayanan Pastoral Gereja Paroki Ampah Peetri dan Paulus - Komas Yogi Ahata; Rhory Valendo (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2024)
The aim of this research is to find out and understand the role and duties of the parish pastoral council in pastoral work and church services in the Catholic Church. The method used in this article is a qualitative research method with data collection techniques using literature reviews, observation, documentation and interviews. The data obtained was analyzed using qualitative methods through data analysis techniques. Research steps include interviews with informants, informant profiles, theme definitions, reflections, implications, synthesis, perspectives or future possibilities. So that the church can grow and develop, with the hope that it can help people to be more active, especially in positions that require service and visits, so that their faith and hope can grow and develop towards eternal salvation, so that they can better understand the meaning contained therein. . in the teachings of the Catholic Church. The results of this research show that the parish pastoral council, especially in Ampa Petrus and Paulus Parish, has a very important role, and the parish pastoral council is very much needed in the parish, especially in pastoral care. from church. and assisting the parish priest in his duties and ministry serving the parishioners.